Back to the Future: The Fathers Refounded and the Recovery of Early Christianity - Young, Robin Darling (Church history, 2020)
The Fathers Refounded, Elizabeth Clark's magnificent sequel to Founding the Fathers, describes in abundant detail how the overlapping disciplines of early church history and patristics became established in several American universities. It examines the work of three historians of early Christianity and their accomplishments and difficulties - and along the way it reminds its readers more than once that historical investigation poses a danger to the security of religious dogmatists. Take, for instance, the work of George LaPiana: As an Italian exile and historical scholar whose investigations of early Christian associations in Rome undermined the accustomed Roman Catholic story of apostolic succession and episcopal authority, his work could be ignored during his lifetime by the triumphalist representatives of seemingly unquestioned dogma. An example is the work of LaPiana's American contemporary, Monsignor Joseph ("Butch") Fenton, writing only a few years before the Second Vatican Council would vindicate the historical approach when it endorsed patristic theology as an inspiration for aggiornamento, the "updating" of Catholic thought.